Republic of Estonia : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Republic of Estonia. (IMF Staff Country Reports; Country Report ;, 2020)
This 2019 Article IV Consultation with Estonia discusses that the outlook is favorable for the near term, however, for slower economic activity for the medium term. Th economy has performed well in recent years, supported by prudent management and effective structural reforms. Growth remains strong and unemployment is at a record low. Inflation is above the euro-area average, consistent with Estonia's convergence process. Wages are rising, reflecting a tight labor market and skill shortages at the high end of the labor market. Absent reforms to boost productivity and manage demographic challenges, however, growth will slow notably. The authorities need to guard against potential overheating in the near term while taking advantage of sizable fiscal buffers in the medium term to support innovation and labor supply and reduce inequality. The report recommends that it is imperative to consider changes that preserve the pension system's viability and sustainability, while promoting policies that address inequality. This includes raising female labor participation through broader implementation of gender pay transparency and flexible childcare arrangements.